Territory, authority, rights : from medieval to global assemblages - Sassen, Saskia (Princeton University Press, 2008)
Where does the nation-state end and globalization begin? In Territory, Authority, Rights, one of the world's leading authorities on globalization shows how the national state made today's global era possible. Saskia Sassen argues that even while globalization is best understood as "denationalization," it continues to be shaped, channeled, and enabled by institutions and networks originally developed with nations in mind, such as the rule of law and respect for private authority. This process of state making produced some of the capabilities enabling the global era. The difference is that these